2013
DOI: 10.1155/2013/514617
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Graphene to Polymer Coatings for Improved Weathering

Abstract: Graphene nanoflakes in different weight percentages were added to polyurethane top coatings, and the coatings were evaluated relative to exposure to two different experimental conditions: one a QUV accelerated weathering cabinet, while the other a corrosion test carried out in a salt spray chamber. After the exposure tests, the surface morphology and chemical structure of the coatings were investigated via atomic force microscopy (AFM) and Fourier transform infrared (FTIR) imaging. Our results show that the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…Numerous theoretical and experimental studies have demonstrated this capability for carbon nanotubes (CNTs) and similar results have been reported for graphene (G), too . Therefore, both CNTs and graphene have been added in small amount to polymer matrix in order to convey the radical scavenging functionalities to the composite film. In most of the cases, when polymer composites containing a few CNT percentage (0.2–5 wt%) are exposed to strong UV irradiation, at higher temperature (50–60 °C) in oxygen atmosphere, the presence of the filler delay the photooxidation process.…”
Section: Introductionmentioning
confidence: 66%
“…Numerous theoretical and experimental studies have demonstrated this capability for carbon nanotubes (CNTs) and similar results have been reported for graphene (G), too . Therefore, both CNTs and graphene have been added in small amount to polymer matrix in order to convey the radical scavenging functionalities to the composite film. In most of the cases, when polymer composites containing a few CNT percentage (0.2–5 wt%) are exposed to strong UV irradiation, at higher temperature (50–60 °C) in oxygen atmosphere, the presence of the filler delay the photooxidation process.…”
Section: Introductionmentioning
confidence: 66%
“…The constancy of crystallinity in the HDPE/graphene nanocomposites may be due to the enhanced stability of the nanocomposites. Graphene can absorb UV radiation and prevent degradation of the polyurethane/graphene coatings …”
Section: Resultsmentioning
confidence: 99%
“…In comparison, possibility of migration and physical loss of nanoparticles from polymeric materials is a difficult task owing to their superior interfacial interaction and less susceptibility towards evaporation or leaching . Literature also reports lower extent of degradation with time in case of nano material filled polymers than the pristine one . Thus, for nanocomposite‐based coating, although the UPF value, before weathering, was lower as compared to Tinuvin B 75, but, loss in UPF value with weathering was also found to be significantly lower.…”
Section: Physical Significancementioning
confidence: 95%